Correction: Corrigendum: PARP3 is a promoter of chromosomal rearrangements and limits G4 DNA - Tovah A. Day (Nature Portfolio, 2017)
Nature Communications 8: Article number: 15110 (2017); Published: 27 Apr 2017; Updated: 13 Jun 2017 In this Article, the antibody ‘BG4’ is consistently referred to incorrectly as ‘hf2’. These errors appear in the Results and Methods. Additionally, the Article incorrectly cites reference 52 in the sentences ‘A recent study described hf2, an engineered single-chain antibody specific for G4 DNA52’ and ‘pSANG10-3F-BG4 (Addgene 55756)52 was transformed into….